HOW UKRAINIAN UNIVERSITY STUDENTS ACADEMICALLY PROCRASTINATE IN CONDITIONS OF FORCED-ONLINE-LEARNING CAUSED BY THE COVID-19 PANDEMIC AND WARTIME - Cherepiekhina, Olha; Turubarova, Anastasiia; Sysoiev, Oleksii; Derevyanko , Nataliya; Bulanov, Valerii (Advanced Education, 2023)
This study aims to investigate the features of academic procrastination among higher education students in the context of forced online learning caused by the COVID-19 pandemic and wartime in Ukraine. Methods. A total of 789 higher education students enrolled in Ukrainian institutions participated in the study, responding to six questionnaires. The research focused on examining the correlation between academic procrastination indicators, self-organization, and the preferred forms of learning during the period of forced online learning. The results indicate that forced online learning has a positive impact on the manifestation of academic procrastination among students and does not promote their self-organization. Significantly higher levels of academic procrastination were observed in students who solely studied online compared to those in the mixed format, involving both online and face-to-face learning. Conversely, students in the mixed format exhibited less pronounced indicators of academic procrastination and higher levels of self-organization and conscientiousness. Moreover, the study identified a new type of academic procrastination labeled as "active academic procrastination." Unlike its negative connotation, this type is perceived as a part of the process of forced online learning. In conclusion, the research expands the theoretical understanding of academic procrastination among students and sheds light on its manifestation during forced online learning. The findings emphasize the importance of considering the learning format's influence on students' procrastination tendencies and offer insights into fostering better self-organization and motivation in the context of online education during challenging circumstances.